1984
DOI: 10.1161/01.hyp.6.2.199
|View full text |Cite
|
Sign up to set email alerts
|

Stability of blood pressure in vegetarians receiving dietary protein supplements.

Abstract: Vegetarians have relatively low blood pressure (BP) levels and consume less protein than do nonvegetarians , and there have been suggestions that certain proteins may raise BP. To determine whether dietary protein supplements raise the BP of vegetarians, 58 g/per day of a 60:40 mixture of soy and wheat proteins and an isocaloric low protein supplement supplying 7 g/day of rice protein were added for 6-week periods to the diet of 18 vegetarians in a 2-group crossover design. Mean daily protein intake during con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Most trials were only small (number of participants per intervention group: n = 7 to n = 30), and the conflicting results may be due to chance findings. [29] [39] In one of the larger trials, a parallel trial in which 121 type 2 diabetes patients received counseling on normal or reduced protein intake, an increase in BP was found (+5.4 mmHg systolic, p = 0.07). [40] However, the low range of intake may have influenced the results.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most trials were only small (number of participants per intervention group: n = 7 to n = 30), and the conflicting results may be due to chance findings. [29] [39] In one of the larger trials, a parallel trial in which 121 type 2 diabetes patients received counseling on normal or reduced protein intake, an increase in BP was found (+5.4 mmHg systolic, p = 0.07). [40] However, the low range of intake may have influenced the results.…”
Section: Resultsmentioning
confidence: 99%
“… [5] This difference of protein effect in subgroups of BP could not be recognized in observational studies. In trials, however, populations with, on average, elevated BP were more sensitive to the BP lowering effect of protein than populations with, on average, normal BP (Out of 9 trials in populations with elevated BP [5] , [29] , [30] , [35] , [37] , [38] , [40] , [42] , [43] 7 trials showed a decrease in BP with high protein intake [5] , [30] , [35] , [37] , [38] , [42] , [43] , whereas out of 7 trials in populations with normal BP [31] [34] , [36] , [39] , [41] only 2 trials [34] , [41] showed a decrease).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vegan protein-based diet has attracted increasing interest in the prevention and treatment of MetS [8,12,17]. In the present study, two different types of vegan protein-based diets—soy diet and gluten-soy mixture diet—were employed in Wistar rats against the control diet (casein diet) to investigate the changes in metabolic parameters and expressions of adiponectin and its receptors in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…After acclimatization for a period of 1 week, rats were randomly assigned into three different groups and given diets containing 20% of one of the following proteins for 12 weeks: casein (CAS, n = 12), soy protein (SOY, n = 12) and wheat gluten-soy mixed protein (GSM, mixing ratio 1:1, n = 12). The 50:50 mixture of soy and wheat protein may be expected to produce an amino acid composition of high biological value based on amino acid content of gluten and soy protein [11,12]. Rat chow diets were prepared based on the Association of Official Analytical Chemists (AOAC) and AIN-93G formulas to meet the nutrient and energy requirements for the growth and development of rats [13].…”
Section: Methodsmentioning
confidence: 99%